Influence of source of nutrition on potato (Solanum tuberosum) tuber quality in elevated temperature storage - BANDANA, BANDANA; KUMAR, DINESH; KUMAR, PARVEEN; RAWAL, SANJAY; SAINI, NEERAJ; SHARMA, VINEET (The Indian Journal of Agricultural Sciences, 2018)
Field experiment was conducted for two years at Central Potato Research Institute Campus, Modipuram to studythe effect of organic+homeopathic and inorganic treatments on potato. Potato (Solanum tuberosum L.) harvestedafter curing were stored at elevated temperature (12Â±0.5oC) with CIPC, (Isopropyl-N-(3-chlorophenyl carbamate) asper modern technology adopted by farmers. The experiment was laid out in sub-plots with three sources of nutrition(organic+homeopathic nutrition) and inorganic treatments and three cultivars Kufri Bahar, Kufri Sindhuri and KufriChipsona-3 in main plots. Results showed that dry matter responded positively to inorganic treatment over organic.Variety Kufri Chipsona 3 recorded maximum dry matter followed by Kufri Sindhuri, while lowest dry matter wasreported in Kufri Bahar. Organic and homeopathic nutrition resulted in significantly superior chip colour as comparedto inorganic treatment. During both the years, potato chips prepared from cv. Kufri Chipsona 3 tubers with organicallytreated one had better chip colour. Organic and homeopathic nutrition significantly reduced mean reducing sugars instored potatoes as compared to inorganic treatment. During both the years of experiment, reducing sugars were lowin organically fertilized potatoes in comparison to inorganically fertilized crop. Mean sucrose content in potatoesstored at this temperature was at par in first year, while significantly lower values were observed in second year ofexperiment in organic+homeopathic treatment. Phenols content were significantly lower in organic and homeopathictreatment over inorganic nutrition across the genotypes in both the years during storage.